2016
DOI: 10.1080/15384101.2016.1188230
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent neurogenic fate of mesenchymal stem cell is determined by Cdk4-mediated hypophosphorylation of Smad-STAT3

Abstract: Cyclin-dependent kinase (Cdk) in complex with a corresponding cyclin plays a pivotal role in neurogenic differentiation. In particular, Cdk4 activity acts as a signaling switch to direct human mesenchymal stem cells (MSCs) to neural transdifferentiation. However, the molecular evidence of how Cdk4 activity converts MSCs to neurogenic lineage remains unknown. Here, we found that Cdk4 inhibition in human MSCs enriches the populations of neural stem and progenitor pools rather than differentiated glial and neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In the present study, we showed miR-145 reduced SMAD3 expression in vitro and in vivo, along with the decrease of Cdk4/Cyclin D1 and XIAP. The results were consistent with the previous report that Cdk4 inhibition dephosphorylated Smads (28). The results suggested that miR-145 worked as a tumor suppressor in acquired regorafenib-resistant colon cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we showed miR-145 reduced SMAD3 expression in vitro and in vivo, along with the decrease of Cdk4/Cyclin D1 and XIAP. The results were consistent with the previous report that Cdk4 inhibition dephosphorylated Smads (28). The results suggested that miR-145 worked as a tumor suppressor in acquired regorafenib-resistant colon cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study showed that CDK4 inhibition directly inactivated Smad1/5/9 and subsequently dephosphorylated STAT3 in human mesenchymal stem cells [ 14 ]. However, our study found that palbociclib had no influence on Smad1/5/9 phosphorylation in H520 and H226 cells ( Figure 4 A and Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several Cdk kinases contain additional motifs in addition to the kinase domain for functional relevance: Cdk12/Cdk13(PITAIRE) 42,43 , Cdk14/Cdk15(PFTAIRE) 23,44 , and Cdk16/Cdk17/Cdk18 (PCTAIRE) [45][46][47] . In addition to their role in the cell cycle, Cdks coordinate with stemness 48 , cell polarity 49,50 , and cell fate specification/determination [51][52][53][54] . Cdk16 (also known as PCTAIRE-1) was previously reported to participate in secretory cargo transport 55 , autophagy 28 , spermatogenesis 28,56 , and tumor proliferation 57 .…”
Section: Discussionmentioning
confidence: 99%